2015
DOI: 10.4081/ijas.2015.3659
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Replacing a Soy Diet withVicia FabaandPisum Sativumon Performance, Meat and Fat Traits ofCinta SenesePigs

Abstract: The aim of this study was to investigate the effect of diets containing genetically modified organism-free legumes as a replacement of soybean on the basis of performance, carcass composition and quality of local pig meat (Cinta Senese). Twenty-four Cinta Senese barrows were divided into 3 dietary groups and were each fed with a diet containing different protein sources: soybean meal (SOY), Vicia faba (FABA) and Pisum sativum (PEA) (8 pigs for each group). The diets were isonitrogenous and isocaloric and conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 26 publications
(48 reference statements)
2
14
0
Order By: Relevance
“…The results obtained are thoroughly evaluated and analysed. Feeds with legume seeds are used to investigate the growth and slaughter parameters of monogastric animals (Zralý et al 2006, 2007, Płazak et al 2012, Sońta et al 2015, 2016 and the qualitative parameters of the slaughter material obtained and the products made (Zralý et al 2006, 2007, Kim et al 2011, Mordenti et al 2012, Hanczakowska and Świątkiewicz 2014, Milczarek and Osek 2014, Sirtori et al 2015. The results of the studies cited above and many other experiments have confirmed the nutritional suitability of legumes for pigs.…”
Section: Introductionmentioning
confidence: 89%
“…The results obtained are thoroughly evaluated and analysed. Feeds with legume seeds are used to investigate the growth and slaughter parameters of monogastric animals (Zralý et al 2006, 2007, Płazak et al 2012, Sońta et al 2015, 2016 and the qualitative parameters of the slaughter material obtained and the products made (Zralý et al 2006, 2007, Kim et al 2011, Mordenti et al 2012, Hanczakowska and Świątkiewicz 2014, Milczarek and Osek 2014, Sirtori et al 2015. The results of the studies cited above and many other experiments have confirmed the nutritional suitability of legumes for pigs.…”
Section: Introductionmentioning
confidence: 89%
“…Curing loss was expressed in percentage and measured as difference between initial weight (time 0) and final weight (14,16 or 18 months depending on seasoning cluster). At the end of each seasoning time (14, 16 or 18 months), ten hams were dissected and on Semimembranosus muscles color (L*, a* and b*) parameters were determined by a Minolta Chromameter CR200 with illuminant C (Tokyo, Japan), immediately after slicing.…”
Section: Physical and Chemical Parametersmentioning
confidence: 99%
“…The salt content was assessed by Volhard method (ISO 1841-1). Fatty acids were determined using a Varian GC-430 apparatus equipped with a flame ionization detector (FID) (Palo Alto, CA, USA) as reported by Sirtori et al, [14]. The individual methyl esters were identified by their retention time using an analytical standard (F.A.M.E.…”
Section: Physical and Chemical Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Broad beans thus also replace some of the grain in the diet when they are substituted for soy. Various studies have found that broad beans can replace a substantial part of the soy in pig as well as cattle diets [45][46][47]. In this study, the calculation of substitution of soy with broad beans and its effect on grain use was based solely on a feeding plan for pigs, as they consume the majority of soy imported to Denmark.…”
Section: Replacing or Reducing Imported Soy In Animal Dietsmentioning
confidence: 99%